Indoor Optical Wireless Receiver – Theory And Design - Abdullah, M.F.L.; Green, R.J (International Journal of Integrated Engineering, 2011)
This paper presents a systematic approach to the design of receiver for indoor optical wireless communication. In particular, it is concerned with how one can properly chooses the front-end preamplifier and biasing circuitry for the photodetector. A comparison between differences types of amplifier, and bandwidth enhancement technique is also discussed. For most photodetector applications, large values of RL and CD would severely restrict bandwidth. It is shown that a proper front-end design incorporates a transimpedance preamplifier which tends to integrate the detector output. Such a design provides significant reduction in photodiode capacitance and increase bandwidth when compared to a design which does not integrate initially. Two novel techniques, using bandwidth adjustment for better service quality with a bootstrapped transimpedance amplifier and bootstrapped composite transimpedance amplifier is presented. A controllable capacitance is introduced at the output of the second stage of the amplifier. These technique permits a bandwidth adjustment from 52Hz to 233MHz for a capacitance range of 10uF to 1pF, while the composite amplifier bandwidth adjustment of the circuit can be controlled in the frequency range of 6MHz to 60MHz for a capacitance range of 50pF to 1nF.